Treatment of Psychosocial Risk Factors in Depression. 2023
DOI: 10.1037/0000332-015
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective social problem solving.

Abstract: C onventional wisdom suggests that the experience of stress is ubiquitous and omnipresent. Conventional wisdom also posits that a modicum of stress is important for our daily lives-if we did not have it, we would not get up in the morning and go to school or work. A further truism (which research findings confirm; e.g., Vrshek-Schallhorn et al., 2020) indicates that too much stress can lead to negative consequences, such as depression. However, we opine that it is not the presence of stress per se that engende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…| 1491 (e.g., Nezu, 1987;Nezu et al, 2004Nezu et al, , 2023. Given these findings, the current study examined both components of social problem-solving among women who experienced IPV with analyses organized into two models (i.e., one for problem orientation and one for problem-solving styles).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…| 1491 (e.g., Nezu, 1987;Nezu et al, 2004Nezu et al, , 2023. Given these findings, the current study examined both components of social problem-solving among women who experienced IPV with analyses organized into two models (i.e., one for problem orientation and one for problem-solving styles).…”
Section: Introductionmentioning
confidence: 99%
“…Social problem‐solving has been deemed an essential social skill, with higher levels of this ability associated with lower symptoms of anxiety and depression, less stress, and lower health risks (e.g., Nezu et al, 2004). Negative problem orientation has been shown to be strongly associated with depression and anxiety, although numerous studies have noted the importance of both impulsive and avoidant styles as well (e.g., Nezu, 1987; Nezu et al, 2004, 2023). Given these findings, the current study examined both components of social problem‐solving among women who experienced IPV with analyses organized into two models (i.e., one for problem orientation and one for problem‐solving styles).…”
Section: Introductionmentioning
confidence: 99%
“…People generate effective solutions to everyday problems through social problem-solving (Chang et al, 2004 ). Patients with depression may employ less effective strategies for interpersonal situations (Chang et al, 2020 ; Nezu et al, 2023 ). In a longitudinal study, Hasegawa et al ( 2018 ) found that rumination and impulsive/careless problem-solving styles intensified depression.…”
mentioning
confidence: 99%